Al Ittijãhãt fi al-Dirãsãt al-Ilmiyyah inda al-Thãlib al-Jãmi’i fi Qismi Ta’lîmi al-Lughah al-Arabiyyah bi Jãmiati Mãdûrã al-Islamiyyah al-Hukûmiyyah - Nurdiana Arifah (OKARA: Jurnal Bahasa dan Sastra, 2019)
Scientific research is one of the students’ contributions to solving problems faced by society now. In the academic years 2014-2015 at the Arabic Language Education department, Tarbiyah Faculty, IAIN Madura, the scientific researches of students are only concentrated in the areas of describing the teaching of the Arabic language. On contrary, today it requires several contributions in solving problems to develop the quality of Arabic language education that participates in the requirements of new education in this globalization era. So, the researcher conducts this research to know their research areas in the Arabic language.  This research is a literary study and the type of research is an analytical descriptive study. The result are 1) percentage of scientific research of students;  22% are in educational techniques, 31.74% are in case study, 12.69% are in education strategies, 7,93% are in educational Media/teaching media, 11.11% are in educational evaluation , 1,58% are in curriculum study , 1,58% is translation , and  the last 3.17% are in content analysis. 2) There are homogeneous definitions between strategies, methods, and techniques in education.